Analisis Pentingnya Online Customer Review Dalam Mempengaruhi Keputusan Pembelian Produk Gadget - Nadeak, Jessica Manna Febriani; Putri, Diana Dyassa; Gunawan, Angeliony Adventri; Gunawan, Andrew; Fauziah, Salma; Ziva, Friska Nuralita; Afifah, Livia Khalishta; Sulistiobudi, Rezki Ashriyana (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim: This study aims to determine the role of online customer reviews in purchase decisions for gadget products on the Shopee marketplace. Design/Methode/Approach: This research used quantitative associative methods and online questionnaires were used to collect research data. Research Finding: The regression analysis using SPSS showed a significant influence between online customer reviews and respondent’s gadget purchase decisions on the Shopee marketplace. Theoretical contribution/Originality: Respondents are more likely react positively to information that is considered trustworthy and honest. Practitioner/Policy implication: This finding is important for sellers and Shopee to improve online customer reviews' quality in increasing gadget product purchases. Research limitation: Due to the utilization of a convenience sampling method and a limited number of participants, the findings from this study cannot be applied to the entire population.